Farm Technology Adoption In Farming:An Application Oftam Model - et. al., A Naga Bhushan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the present study we analyze the farmers’ perception towards adoption of technology such as technology adoption for better productivity in farming. The considered constructs are adopted from Technology adoption model (TAM). A total sample of 165seasonal farmers who grow millets from the Guntur district are considered through simple random technique and out of which survey respondents irregular responses are eliminated finally 150 samples are determined for statistical analysis. Factor analysis was performed to determine the latent factors and their dependent association with intention for adoption was observed with regression analysis. Results are reported and discussions are made as per the results and in correlation between results and previous literature and finally, suggestions and future indication for extension of the study are proposed.